Friendship and relationships between members of the middle classes in Cali - Sánchez, José Fernando (2016)
This article describes the main tests faced by individuals belonging to the middle classes in Cali, in the framework of its relations of friendship and couple. These challenges that affect different areas of your personal life, work and family are part of the relational dynamics that characterized such groups and that are the product of the economic, political and cultural transformations that have characterized the recent history of Colombian society.